2016
DOI: 10.3892/mmr.2016.5249
|View full text |Cite
|
Sign up to set email alerts
|

Alisertib induces apoptosis and autophagy through targeting the AKT/mTOR/AMPK/p38 pathway in leukemic cells

Abstract: Alisertib, a potent and selective Aurora kinase A inhibitor, has been demonstrated to exert potent anti-cancer effects in pre-clinical and clinical studies. However, mechanisms of action of alisertib, including the molecular pathways involved in alisertib-induced apoptosis and autophagy of leukemic cells, have remained elusive. The aim of the present study was to investigate the effects of alisertib on cell growth, apoptosis and autophagy and to delineate the possible molecular mechanisms in leukemic cells. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…It has been demonstrated that aurora B kinase, which exists in a complex with survivin and mTOR, synergistically regulates survival and proliferation of leukemia and lymphoma cells via crass-talk with AKT, mTOR and NOTCH signaling pathways (73,74). Moreover, several studies have reported that aurora kinase inhibitors induce cell-cycle arrest and apoptosis of cancer cells through p38 MAPK and AKT/mTOR signaling (75,76). Therefore, the synergistic cytotoxicity of the combination of barasertib plus melatonin towards leukemia lymphocytes could be explained by amplification of the effects of both substances on both molecular targets -aurora B kinase and mTOR.…”
Section: Effect Of Melatonin On Barasertib-induced Cytotoxicity Apopmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that aurora B kinase, which exists in a complex with survivin and mTOR, synergistically regulates survival and proliferation of leukemia and lymphoma cells via crass-talk with AKT, mTOR and NOTCH signaling pathways (73,74). Moreover, several studies have reported that aurora kinase inhibitors induce cell-cycle arrest and apoptosis of cancer cells through p38 MAPK and AKT/mTOR signaling (75,76). Therefore, the synergistic cytotoxicity of the combination of barasertib plus melatonin towards leukemia lymphocytes could be explained by amplification of the effects of both substances on both molecular targets -aurora B kinase and mTOR.…”
Section: Effect Of Melatonin On Barasertib-induced Cytotoxicity Apopmentioning
confidence: 99%
“…In conclusion, there are many data regarding sensitization of cancer cells to conventional anticancer drugs (such as doxorubicin, bleomycin, cisplatin) by melatonin (34,46,47,(53)(54)(55)(56)(57), but only a limited number of studies have described the effect of melatonin on the cytotoxicity of new-generation anticancer drugs (recently approved for clinical use or still in clinical trials) (75)(76)(77). There are no data about the effect of melatonin on the efficiency of new-generation anticancer drugs described in the present study: AZD7762 (a selective inhibitor of checkpoint kinases), ABT-737 (a selective inhibitor of BCL2 proteins), barasertib (a selective inhibitor of aurora B kinase), everolimus (mTOR inhibitor), lonafarnib (a farnesyltrasferase inhibitor), MG132, MLN-2238 and bortezomib (proteasome inhibitors), and palbociclib (a selective inhibitor of cyclindependent kinases).…”
Section: Effect Of Melatonin On Barasertib-induced Cytotoxicity Apopmentioning
confidence: 99%
“…The regulation of autophagy is complicated which involves multiple signal pathways, including mechanistic target of rapamycin (mTOR), AMP-activated protein kinase (AMPK), nuclear factor (NF)-κB, and mitogen-activated protein kinase (MAPK)-mediated signaling pathway etc. [ 12 14 ]. The renewal of mitochondria depends on autophagy, yet the relationship amongst autophagy, ROS signal, and mitochondrial dysfunction is still not clear; but when autophagy is blocked, the aggregation of toxic protein and mitochondrial dysfunction will further aggravate oxidative stress [ 4 , 10 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is generally believed to be a “double-edged sword” that controls the fate of cells because it not only helps cell survive during nutrient deprivations or other stresses, but also jeopardizes cells and induces cell death. In some cells, such as breast cancer cells 8 , leukemic cells 9 and neurons 10 , autophagy and apoptosis cooperate to regulate cell survival and death. However, whether apoptosis and autophagy of neutrophils in SIRS are positivlye or negatively correlated, and whether some molecules can regulate the two essential processes synergistically are not clear.…”
mentioning
confidence: 99%